Outcomes of Naturopathy and Yoga intervention on 24-hour ambulatory blood pressure among primary hypertensives: A cohort study - Rai, Abhijna; HC , Shashikiran; Dinesh, Sujatha; Shetty, Prashanth; Pakkala, Navin (Indian Journal of Integrative Medicine, 2024)
Objectives: Naturopathy and yoga an efficient treatment modality used in the prevention and management of many chronic lifestyle ailments. This study has been done to assess the outcomes of naturopathy and yoga intervention on 24-hour ambulatory blood pressure. Methods: For the research, 66 pre-diagnosed primary hypertension individuals between the ages of 30 and 60 were included. Subjects were assessed for 24 hours of ambulatory blood pressure (ABP), anthropometry, and WHRQOL questionnaire (World health-related quality of life) short form (SF-36) on the first and tenth day of their stay in the hospital. Results: This study results showed there was a significant reduction in the mean value of 24-hour SBP (p